Back to Bataan - Dmytryk, Edward; Warner Bros.; Dolby Digital; RKO Radio Pictures, Inc. (Burbank, CA Turner Entertainment Co., 2007)
1942, The Philippines. Enemy forces take control of the island nation. But as one type of war ends, another begins. Col. Joseph madden and others like him organize uncaptured Amefrican troops and Philippine fighters into effective guerrilla-warfare operatives.
With equal parts grit and patriotic zeal, John Wayne protrays Madden in this heroic salute to the Philippine resistance forces who continued the fight in the years leading to McArthur's return. Among the true life incidents in the film's morale-boosting narrative is the liberation of prisoners from Cabanatuan - an event underscored by an onscreen roll call of real life U.S. Soldiers freed by that daring rescue. Seeing these haunted but happy faces was a touching moment for audiences then. It remains so today.
RKO Radio Pictures, Inc. presents John Wayne in Back to Bataan with Anthony Quinn, Beulah Bondi ; Executive Producer, Robert Fellows ; Screenpaly by Ben Barzman and Richard H. landau ; Directed by Edward Dmytryk.
Standard version presented in a format preserving the aspect ratio of its original thearitical exhibition.
Subtitles: English, Fracais, Espanol (Feature Film Only)
Back to Bataan copyright RKO Pictures, Inc., Package Design & Supplementary Material Compilation copyright 2007, Turner Entertainment Co. and Warner Bros. Entertainment Inc., Distributed by Warner Home Video, 4000 Warner Blvd. Burbank, CA. 91527. All rights reserved. "Dolby" and the DD symbol are trademarks of Dolby LaboratoriesLicensing.
Burned from the original copy of F. Villanueva
Keywords: History -- Philippines; World war, 1939-1945 -- Campains -- Philippines&xBataan (Province) -- Drama; Guerrilla warfare -- Philippines -- Bataan (Province) -- Drama; Bataan (Philippines: Province) -- Drama; War Films; World war, 1939-1945 -- Underground movements -- Philippines&xBataan (Province) -- Drama